A study on manpower and productivity issues of warehouses and distribution centres in Singapore - Chen, Shao (2014)
In coping with increasing pressure to restrict foreign labour in Singapore, the government implemented cooling measures such as the foreign worker levy and dependency ratio ceiling. This as we found out has raised business costs and created problems for enterprises, especially in the sector of warehousing and distribution. To cushion the negative repercussions, the government offered various levels of incentives for SMEs to tap onto, ranging from heavily subsidised equipment and tax rebates, to bite sized co-funding of ICT and energy saving adoptions. Our project aimed to study and analyse the receptiveness of various schemes from the point of view of warehouses and DCs. We also aimed to study government agencies to understand deeper the intentions in laying out these schemes for enterprises.